2018
DOI: 10.1590/0001-3765201820170914
|View full text |Cite
|
Sign up to set email alerts
|

Wollastonite to hinder growth of Aspergillus niger fungus on cotton textile

Abstract: Effects of Aspergillus niger was investigated on the strength of cotton textile specimens impregnated with nano-wollastonite, and then compared with normal specimens. Cotton strips were cut and prepared in warp and wept directions according to the standard specifications ASTM D-5035. Results showed that incubation of A. niger on specimens for three months resulted in a significant decrease in tensile stress as well as weight mass change in both directions. Impregnating specimens with NW ameliorated the negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(10 reference statements)
1
13
0
Order By: Relevance
“…The increase was attributed to the deteriorating effect of Aspergillus niger on textile fibers, decreasing their integrity and eventually, allowing a larger volume of air to pass through. The same deteriorating effect was reported to have caused considerable decline in tensile stress of cotton textile [18]. The similar increase in fluid flow rate in the control and NW-10% specimens indicated that 10% of NW is not enough to significantly hinder the growth of A. niger on cotton textile.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…The increase was attributed to the deteriorating effect of Aspergillus niger on textile fibers, decreasing their integrity and eventually, allowing a larger volume of air to pass through. The same deteriorating effect was reported to have caused considerable decline in tensile stress of cotton textile [18]. The similar increase in fluid flow rate in the control and NW-10% specimens indicated that 10% of NW is not enough to significantly hinder the growth of A. niger on cotton textile.…”
Section: Resultssupporting
confidence: 63%
“…The r-square value of 66% between fluid flow values versus tensile stress indicated that although fluid flow in cotton textile as a porous media was closely in relation with the integrity of the overall matrix, other elements were also involved in the process (Figure 10). In this connection, considering highly significant decreasing effect of fungal exposure on tensile stress and tensile strain values in a previous study [18], higher increase in fluid flow was expected. However, it is to be noted that growth of thick mycelium network on and within voids and spaces of control specimens partially blocked the way through transfer of fluid (Figure 9a).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Nanotechnology has been reported to improve the properties and eliminate some drawbacks in many composites and materials [9][10][11][12][13], although changes can occur in the material properties when the size range is reduced to nanometer scale [14]. For wood and wood-composites, different nanomaterials were utilized to further improve fire retardancy, biological resistance, water repellency, and mechanical properties [15][16][17][18][19][20][21][22][23]. Recently, nanowollastonite was applied with urea formaldehyde resin, which improved the thermal conductivity coefficient and, consequently, the mechanical and physical properties of OSL [12].…”
Section: Introductionmentioning
confidence: 99%